2010
DOI: 10.1002/jbmr.180
|View full text |Cite
|
Sign up to set email alerts
|

Bone material properties in actively bone-forming trabeculae in postmenopausal women with osteoporosis after three years of treatment with once-yearly Zoledronic acid

Abstract: Zoledronic acid (ZOL), a third-generation aminobisphosphonate, showed pronounced antifracture efficacy in a phase III clinical trial [Health Outcomes and Reduced Incidence with Zoledronic Acid Once Yearly-Pivotal Fracture Trial (HORIZON-PFT)] when administered yearly (5-mg infusions of ZOL), producing significant reductions in morphometric vertebral, clinical vertebral, hip, and nonvertebral fractures by 70%, 77%, 41%, and 25%, respectively, over a 3-year period. The purpose of this study was to analyze the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 35 publications
5
56
1
2
Order By: Relevance
“…(25,34) The analysis of iliac crest bone biopsies performed in a subset of HORIZON trial patients by mCT identified significantly better preservation of trabecular structure with ZOL than with PLB (26) and microspectroscopy analysis of these biopsies showed an increased mineral/matrix ratio with a larger proportion of younger bone tissue with ZOL compared with PLB. (36) These findings suggest that ZOL may exert its fracture risk reduction effects by increasing bone mass and by preserving bone quality in terms of bone microarchitecture and bone material properties. These findings are consistent with the improvements in TBS versus baseline observed with ZOL but not with PLB over 3 years.…”
Section: Discussionmentioning
confidence: 85%
“…(25,34) The analysis of iliac crest bone biopsies performed in a subset of HORIZON trial patients by mCT identified significantly better preservation of trabecular structure with ZOL than with PLB (26) and microspectroscopy analysis of these biopsies showed an increased mineral/matrix ratio with a larger proportion of younger bone tissue with ZOL compared with PLB. (36) These findings suggest that ZOL may exert its fracture risk reduction effects by increasing bone mass and by preserving bone quality in terms of bone microarchitecture and bone material properties. These findings are consistent with the improvements in TBS versus baseline observed with ZOL but not with PLB over 3 years.…”
Section: Discussionmentioning
confidence: 85%
“…As one of the diseases predominantly presenting in the elderly, an increasing number of individuals suffer from osteoporosis and osteoporotic fractures as a result of the increase in the elderly population (21). Osteoporosis has already become a problem for healthcare in the aging population; however, it has yet to attract sufficient research attention (22).…”
Section: Discussionmentioning
confidence: 99%
“…(11,25) In the present study, areas adjacent to fluorescent tetracycline labels were analyzed, ensuring that tissue of similar age was analyzed, thus rendering the results bone turnoverindependent. (14) Mineral/matrix ratio is a measure of bone density, which unlike BMD expresses the amount of mineral per amount of matrix (mainly type I collagen) per volume analyzed (25) and reflects bone ash weight. (41) In a recent report it was shown to be a better predictor of bending stiffness than BMD.…”
Section: Discussionmentioning
confidence: 99%
“…For the biopsies in which only one label was discernible, casting doubt as to whether it was the first or the second one, we analyzed areas that had around 10 mm distance between the label and the mineralizing front. (14) In these cases, spectra were recorded 2 mm from the label, in the area between the label and the mineralizing front.…”
Section: Anatomical Area Selection For Spectroscopic Analysismentioning
confidence: 99%